Human resource information systems research in transition: A global bibliometric mapping of knowledge, collaboration, and future direction - Setyorini, Noni; Nastiti, Prianka Ratri; Fathurachman, Chadyan; Suniroh, Siti (Asian Management and Business Review, 2026)
This study aims to provide a comprehensive overview of the intellectual and thematic evolution of human resource information systems (HRIS) research within the context of digital transformation. Despite its growing strategic importance, HRIS literature remains fragmented across theoretical, methodological, and geographical dimensions. This study seeks to map the structural dynamics, emerging themes, and future research trajectories shaping the field. A bibliometric and science mapping approach was employed using data extracted from 303 peer-reviewed articles (1990–2025) indexed in the Scopus database. The analysis utilized VOSviewer and Biblioshiny (R Bibliometrix) to examine publication performance, co-authorship networks, citation patterns, and keyword co-occurrences, offering an evidence-based assessment of the intellectual landscape of HRIS research. Results reveal the transition of HRIS from a technology-centric system to a strategic and human-centered digital capability, emphasizing themes such as digital transformation, HR analytics, employee trust, and organizational agility. The study identifies key theoretical clusters, influential authors, and global collaboration patterns while exposing persistent gaps related to conceptual integration, methodological diversity, and regional representation. The findings provide valuable insights for scholars, practitioners, and policymakers to strengthen theoretical coherence, promote interdisciplinary collaboration, and enhance HRIS-driven digital capability within organizations. This study is among the first to offer a global, longitudinal bibliometric synthesis of HRIS research, presenting an integrative framework that links technological innovation, strategic human resource management, and knowledge-based organizational development.